The relation of Kansas climate to the increased productivity of the state - Gish, Oliver H. (My University, 1908)
Introduction: Kansas, a portion of the great western plains, once considered incapable of sustaining a civilized society, now one of the foremost agricultural states in the United States, presents a marked transformation, the cause of which has at times been a source of considerable conjecture.
Citation: Gish, Oliver H. The relation of Kansas climate to the increased productivity of the state. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Kansas; Climate; Weather; Graduating theses; Senior theses; Theses